The Impact of Implementation of an ICU Consult Service on Hospital-Wide Outcomes and ICU-Specific Outcomes. (August 2016) - Al-Rajhi, Amjad; Mardini, Louay; Jayaraman, Dev
Background: Rapid response teams (RRTs) were developed to promote assessment of and early intervention for clinically deteriorating hospitalized patients. Although the ideal composition of RRTs is not known, their implementation does require significant resources. Objective: To test the effectiveness of a dedicated daytime/weekday intensive care unit (ICU) consult service without formal training of ward teams. Methods: Pre- and postintervention study with weekends/nights during implementation period acting as a concurrent control.Setting: An adult tertiary care university center in Montreal without an RRT.Intervention: A daytime/weekday ICU consult service with a dedicated intensivist. Results: Total hospital mortality rate did not differ between the control and the implementation period (6.65% vs 6.60%; P = .84). The hospital code blue rates also did not differ (1.21/1000 vs 1.14/1000 patient days; P = .58). In contrast, 30-day mortality of patients admitted to the ICU following an ICU consult decreased (39% vs 24% P = .01). Multivariate analysis confirmed this effect on 30-day mortality (odds ratio for implementation period: 0.53 [95% confidence interval: 0.33-0.85] P = .009). The 14-day ICU readmission rate was reduced with the intervention (5.1% vs 4.1%; P < .001). The effect on 30-day mortality and ICU readmissions were only present during daytime/weekdays. Conclusion: Implementation of an ICU consult service without any formal afferent limb training was associated with decreased mortality and 14-day readmission rates of patients admitted to the ICU. In contrast, hospital-wide mortality and code blue rates were unaffected.